MASTICATION, PHONETICS AND ESTHETICS AS A FINAL RESULT OF PARTIAL OR COMPLETE DENTURE TREATMENT. - Kalina Georgieva; Iveta Katreva; Metodi Abadjiev (Peytchinski Publishing, 2015)
Three target groups- dentists/ dental students, dental technicians and patients were asked to fill in an anonymous questionnaire about their satisfaction of the final results after prosthetic treatment with removable dentures using a scale from 1 to 5 (1- completely dissatisfied, 2-dissatisfied, 3-indifferent, 4-satisfied, 5-completely satisfied). The mean results (including colour, shape and size of artificial teeth, arrangement of front teeth, colour of artificial gums, phonetics, mastication, natural smile, enough space for tongue) for all three groups of respondents were compared. Dental technicians (4,34) are more satisfied than dentists/dental students (3,62) and patients (3,53). A successful outcome of prosthetic treatment depends on one hand on the professional approach of the dental team and on the other hand on the patient's motivation and cooperation. The predictive final results and realistic expectations lead to satisfaction of all participants in the treatment process.